Characterization of patients with chronic pulmonary aspergillosis according to the new ESCMID/ERS/ECMM and IDSA guidelines. Issue 2 (1st December 2016) - Salzer, Helmut J. F.; Heyckendorf, Jan; Kalsdorf, Barbara; Rolling, Thierry; Lange, Christoph
Summary: Recently, the Infectious Diseases Society of America (IDSA) and the European Society for Clinical Microbiology and Infectious Diseases (ESCMID) in cooperation with the European Respiratory Society (ERS) and the European Confederation of Medical Mycology (ECMM) published guidelines for the diagnosis of chronic pulmonary aspergillosis (CPA). Both guidelines, however, carry significant differences. We retrospectively applied the diagnostic recommendations on a patient cohort of 71 previously diagnosed CPA patients in order to compare both guidelines. In 50 patients (70%) the diagnosis was confirmed by the diagnostic criteria of both guidelines, while nine patients (13%) fulfilled neither the ESCMID/ERS/ECMM nor the IDSA criteria. Reasons were lack of mycological evidence in respiratory samples. These patients were not tested for the presence of Aspergillus ‐specific IgG antibodies, which is strongly recommended by both guidelines. Seven patients did not fulfil the diagnostic criteria of the IDSA guideline, because of severe immunosuppression, while five patients didn't fulfil the diagnostic criteria of the ESCMID/ERS/ECMM guideline, because of uncommon image findings. The comparison of both guidelines highlight that the combination of a chest CT scan with the performance of an Aspergillus ‐specific IgG antibody assay are key diagnostic features to establish a guideline‐based diagnosis of CPA.